Endocannabinoid modulation of homeostatic and non-homeostatic feeding circuits. (15th September 2017) - Lau, Benjamin K.; Cota, Daniela; Cristino, Luigia; Borgland, Stephanie L.
Abstract: The endocannabinoid system has emerged as a key player in the control of eating. Endocannabinoids, including 2-arachidonoylglycerol (2-AG) and anandamide (AEA), modulate neuronal activity via cannabinoid 1 receptors (CB1Rs) in multiple nuclei of the hypothalamus to induce or inhibit food intake depending on nutritional and hormonal status, suggesting that endocannabinoids may act in the hypothalamus to integrate different types of signals informing about the animal's energy needs. In the mesocorticolimbic system, (endo)cannabinoids modulate synaptic transmission to promote dopamine release in response to palatable food. In addition, (endo)cannabinoids act within the nucleus accumbens to increase food's hedonic impact; although this effect depends on activation of CB1Rs at excitatory, but not inhibitory inputs in the nucleus accumbens. While hyperactivation of the endocannabinoid system is typically associated with overeating and obesity, much evidence has emerged in recent years suggesting a more complicated system than first thought – endocannabinoids promote or suppress feeding depending on cell and input type, or modulation by various neuronal or hormonal signals. This review presents our latest knowledge of the endocannabinoid system in non-homeostatic and homeostatic feeding circuits. In particular, we discuss the functional role and cellular mechanism of action by endocannabinoids within the hypothalamus and mesocorticolimbic system, and how these are modulated by neuropeptide signals related to feeding. In light of recent advances and complexity in the field, we review cannabinoid-based therapeutic strategies for the treatment of obesity and how peripheral restriction of CB1R antagonists may provide a different mechanism of weight loss without the central adverse effects. This article is part of the Special Issue entitled "A New Dawn in Cannabinoid Neurobiology". Graphical abstract: Endocannabinoid modulation of the mesocorticolimbic and hypothalamic circuits: a highly interconnected circuit of excitatory (glutamatergic) and inhibitory (GABAergic) pathways exist between the ventral tegmental area (VTA), nucleus accumbens (NAc), medial prefrontal cortex (mPFC) and hypothalamus (Hyp). Furthermore, the VTA sends prominent dopamine projections to the NAc and mPFC. A number of synaptic inputs onto principal neurons within the VTA (dopamine neurons), NAc (medium spiny neurons), mPFC (pyramidal neurons) and hypothalamus express CB1 receptors, and are sensitive to endocannabinoid-mediated, short-term plasticity (DSI/DSE) and/or long-term plasticity (LTD/iLTD) in naive animals. Exposure to a palatable/high-fat diet (or omega-3 deficient diet) or the development of diet-induced obesity can alter these forms of synaptic plasticity [Insets: +/− indicates present/absent, while ↑/↓/ = /? indicate increase/decrease/no change/unknown, respectively]. Highlights: Endocannabinoids act in multiple hypothalamic nuclei to integrate signals informing about the animal's energy needs. Endocannabinoids modulate synaptic transmission in the VTA and NAc to promote dopamine release in response to palatable food. Peripherally restricted cannabinoid receptor antagonists may be therapeutic in the treatment of obesity.